Beyond Lalonde: creating health - Buck, Carol (Journal of Public Health Policy Ins. BurlingtonUS)
Argues that the most important of four elements in Lalonde's Health Field concept is the environment. Notes that if the environment is wrong, the elements of human biology, lifestyle and health care organization will be wrong also. Reviews the factors which must be changed if health is to be improved.